Debunking "fake news" on social media: Short-term and longer-term effects of fact checking and media literacy interventions - Lara Marie Berger; Anna Kerkhof; Felix Mindl; Johannes Münster (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2023)
We conduct a randomized survey experiment to compare the short- and longer-term effects of fact checking to a brief media literacy intervention. We show that the impact of fact checking is limited to the corrected fake news, whereas media literacy helps to distinguish between false and correct information more generally, both immediately and two weeks after the intervention. A plausible mechanism is that media literacy enables participants to critically evaluate social media postings, while fact checking fails to enhance their skills. Our results promote media literacy as an effective tool to fight fake news, that is cheap, scalable, and easy-to-implement.
Keywords: L51; L82; Z18; 330; Covid; Facebook; fact checking; fake news; media literacy; misinformation; nutrition; social media; supplements; survey experiment; vaccine